Pengaruh Kualitas Pelayanan dan Citra Merk Terhadap Keputusan Menabung Pada Bank Papua Kantor Cabang Abepura Melalui Word Of Mouth Sebagai Variabel Intervening - Hendra Gunawan; Muhammad Nasir Hamzah; Jamal Irawan Widyanardy (Movere Journal, 2026)
This study aims to analyze the influence of service quality and brand image on saving decisions, with word of mouth (WOM) serving as an intervening variable at Bank Papua, Abepura Branch. In a marketing context, saving decisions are influenced by various factors, including service quality, brand image, and word of mouth. This research adopts a quantitative approach using survey methods and data analysis via Structural Equation Modeling (SEM). The results demonstrate that service quality has a significant positive influence on saving decisions; brand image has a significant positive influence on saving decisions; and word of mouth has a significant positive influence on saving decisions. Furthermore, service quality has a significant positive influence on word of mouth, and brand image has a significant positive influence on word of mouth. Service quality and brand image both exhibit a significant positive influence on saving decisions through word of mouth as an intervening variable. These findings provide a significant contribution to marketing, particularly in designing service quality and brand image programs to optimize saving decisions. Additionally, this study offers practical implications for management in formulating policies that can enhance saving decisions through the continuous optimization of service quality and brand image.